Identifying Barriers to Development of the Public-Private Partnership in Providing of Hospital Services in Iran:A Qualitative Study - Ahmad Sadeghi; Peivand Bastani; Omid Barati (Shahid Sadoughi University of Medical Sciences, 2020)
Background: In recent years, public-private partnerships (PPPs) have been used to expand hospital services in many countries. Despite the achievements and implications, there have always been many challenges in implementing it. The purpose of this study was to identify the barriers and challenges in the development of public-private partnerships in hospital services in the country of Iran. Methods: This is a qualitative study conducted in 2015- 2016 by the content analysis method. The research population included experts and health professionals and those who have contributed to the development of PPPs model in hospital services (public and private). Of these, eighteen were selected using a purposive sampling approach and were interviewed semi-structured. The MAXQDA10 software was used to analyze the transcribed interviews. Results: Four main themes and sixteen sub-themes were identified concerning the barriers to developing public-private partnerships in the provision of hospital services in the country. They are cultural and social barriers, political and legal barriers, financial and investment barriers, and structural and process barriers. Conclusion: Officials and policymakers should identify the obstacles facing participatory patterns and then provide a suitable platform for nongovernmental organizations. This action can lead to an increase in the level of readiness of hospitals in Iran to implement this model.